2014
DOI: 10.1161/circheartfailure.113.000792
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Determinants, and Prognostic Significance of Hyperkalemia and Worsening Renal Function in Patients With Heart Failure Receiving the Mineralocorticoid Receptor Antagonist Eplerenone or Placebo in Addition to Optimal Medical Therapy

Abstract: Background— Mineralocorticoid receptor antagonists improve outcomes in patients with systolic heart failure but may induce worsening of renal function (WRF) and hyperkalemia (HK). We assessed the risk factors for mineralocorticoid receptor antagonist–related WRF and for HK, as well as the association between HK and WRF with clinical outcomes in the Eplerenone in Mild Patients Hospitalization and Survival Study in Heart Failure (EMPHASIS-HF). Methods and Results— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
172
1
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 218 publications
(197 citation statements)
references
References 23 publications
16
172
1
8
Order By: Relevance
“…Eplerenone, however, was safe in carefully monitored risk patients in a substudy of EMPHASIS‐HF 29. In a subanalysis of RALES, the absolute benefit of spironolactone was greatest in patients with reduced kidney function30 and a subanalysis from EMPHASIS‐HF showed positive effect on survival despite worsening renal function 31. Our findings support that MRA may be used in patients with MI and HF, even in the presence of CKD.…”
Section: Discussionsupporting
confidence: 56%
“…Eplerenone, however, was safe in carefully monitored risk patients in a substudy of EMPHASIS‐HF 29. In a subanalysis of RALES, the absolute benefit of spironolactone was greatest in patients with reduced kidney function30 and a subanalysis from EMPHASIS‐HF showed positive effect on survival despite worsening renal function 31. Our findings support that MRA may be used in patients with MI and HF, even in the presence of CKD.…”
Section: Discussionsupporting
confidence: 56%
“…7 Previous analyses in HF noted poorer outcomes in patients with potassium levels below 4.0 mmol/L, 8,9 and incident hypokalemia may be potentially attenuated by the use of MRAs. An analysis of the Eplerenone in Mild Patients Hospitalization and Survival Study in Heart Failure (EMPHASIS-HF) study showed that clinical benefits with eplerenone remained even in those who developed hyperkalemia, 10 but whether elevations in potassium levels reduce the clinical benefit observed with MRAs in patients with severe HF is unknown.…”
Section: Clinical Perspective On P 579mentioning
confidence: 99%
“…7 Together, the findings in patients from the Americas enrolled in TOPCAT substantiate the concept that there could be a true pathophysiological continuum from HF-PEF to HF-REF involving cardiorenal interactions and response profiles similar to RAAS inhibition therapy, with increased rates of worsening renal function and hyperkalemia in patients from the Americas treated with MRA, albeit with better clinical outcomes. Similarly, although a serum potassium level >5 mmol/L has been shown to be associated with an increase in cardiovascular deaths in patients with HF-REF without or with chronic kidney disease, trials have shown that patients with HF-REF receiving an angiotensin-converting enzyme inhibitor, an angiotensin receptor antagonist, or an MRA (spironolactone or eplerenone) have better clinical outcomes despite experiencing more frequent episodes of hyperkalemia [8][9][10] and or worsening renal function 8,9 shortly after RAAS inhibitor initiation or thereafter. In HEAAL (Heart Failure End Point Evaluation of Angiotensin II Antagonist Losartan) 8 and EMPHASIS-HF (Eplerenone in Mild Patients Hospitalization and Survival Study in Heart Failure), 10 high-dose losartan or eplerenone was associated with more frequent worsening renal function and hyperkalemia than low-dose losartan or placebo, respectively.…”
Section: Articles See P 34 and P 43mentioning
confidence: 99%